Assessment of transformer health index using different model - Jasni, Jasronita; Azmi, Akmalina; Azis, Norhafiz; Yahaya, Muhammad Sharil; Talib, Mohd Aizam (Universiti Putra Malaysia Press, 2017)
Transformer failures lead to interruption of power supply. Therefore, asset management is important to monitor the efficient functioning of transformers. An important approach in asset management is condition assessment whereby the health status of the transformer is assessed via a health index. There are many methods in determining the final value of a health index. This paper examines how different assessment methods can be used in order to come up with the final health index and output of final health index. The output trend shapes are almost the same for Assessment Model A, B and C except for Assessment Model D. There is no strong correlation between the health index and age of the transformer. Generally, the value of health index of the transformer is reflected by its operation and loading history .This paper hence examines the assessment steps and results that will guide the development of a new approach to determine health index value.